KEPENARIAN TOKOH KEN DEDES DALAM KEN DEDES: THE SOLILOQUY KARYA MATHEUS WASI BANTOLO - Dea Putri Komala Sari; Matheus Wasi Bantolo (Institut Seni Indonesia Surakarta, 2019)
The fullness of the work of Ken Dedes: The Soliloquy is an interpretation of a female character named Ken Dedes from the work of Arok The Godfather’s Soliloquy of Matheus Wasi Bantolo. The study discusses the process and forms of fullness from Ken Dedes: the Soliloquy. To describe this, several concepts were used: In reviewing the fullness of matter using the concept of Alma Hawkins, to describe the form of opera using the concept of Peter Sellars and Matheus Wasi Bantolo, while describing the form of In the works using the Suzane K Langer concept is reinforced by the concept of dance analysis according to Janet Adshead. Writing and reviewing using qualitative methods that are descriptive interpretative, with the observation process participant action research. Results of this study showed that the fullness process conducted based on the process of exploration, improvisation and composition as a stage of the work of the fullness of Ken Dedes: the Soliloquy. The present form of presentation is a new interpretation of the character Ken Dedes in the work of Arok The Godfather’s Soliloquy. The fullness of Ken Dedes: The Soliloquy has a form of dish with an opera concept that uses five dancers who each have dual roles as dancers and musicians. Many movements adopted the movement of Javanese traditions in Surakarta style by combining the elements of Latin dance motion in them. It is based on the thought of choreographer to elaborate on The character Ken Dedes as a woman in the past with female figures in The Godfather film and female figures at present. The fullness of the work of Ken Dedes: The Soliloquy has a perspective on how Ken Dedes as women with the various problems faced can be aligned with women today. Keywords: fullness, character Ken Dedes, Opera.